PEMBAYARAN KLAIM OLEH PERUSAHAAN AJB BUMIPUTERA 1912 DALAM HAL TERJADINYA WANPRESTASI OLEH TERTANGGUNG PADA PROGRAM MITRA BEASISWA - Aditya Mantara Putra, I Made; Agung, I Gusti Nyoman; Dedy Priyanto, I Made (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 11, November 2013)
This paper has the title " Payment of claims by the Perusahaan AJB Bumiputera 1912 in the case of a default by the insured in the partner program scholarship plan " . The research method used in this paper is the Juridical Empirical , namely a state research gap das solen ( theory ) and das sein ( practice or reality ) that the gap between the theoretical state of the legal facts . In this paper , the issue raised is why the Perusahaan AJB Bumiputera 1912 pleaded no cancellation insurance agreement to the judge in the case of a default by the insured and how the payment of claims against the insured who are in default . The conclusion is AJB Bumiputera 1912 the Company did not plead to the judge because the cancellation is costing , time as well as a great power , so its cancellation can be done by both parties only and on payment of a claim , the policy will only be made if the insured already has a cash value .
Keywords: Claim, Premium Payment, Insured, Default